2022
DOI: 10.1111/are.15823
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of fish oil with black soldier fly larvae oil and vegetable oils: Effects of growth, whole‐body fatty acid profile, digestive enzyme activity, haemato‐biochemical responses and muscle growth‐related gene expression of juvenile striped catfish, Pangasianodon hypophthalmus

Abstract: A 10‐week feeding trial was conducted to evaluate the effects of dietary replacement of fish oil (FO) with black soldier fly larvae oil (BSFLO) and vegetable oils, namely moringa oil (MO), black cumin seed oil (BCSO) and flax seed oil (FSO) on growth and whole‐body fatty acid profile, digestive enzyme activity, haemato‐biochemical responses and muscle growth‐related gene expression of juvenile striped catfish, Pangasianodon hypophthalmus. Five isonitrogenous (313.34 g kg−1) and isolipidic (81.82 g kg−1) experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…It is interesting to note that the dietary adjustments had no effect on the digestion of the majority of n−3 fatty acids (18:4n−3, 20:5n−3, 22:5n−3, and total n−3 fatty acids). Regarding the dietary insect oil inclusion effect on digestive enzyme activity in fish, Sudha et al 79 recently reported no significant change on amylase, lipase and protease activity in the intestine and liver of stripped catfish fed BSFLO compared with FO, MO, BCSO and FSO. Similar to this, Belghit et al 17 showed that dietary inclusion of insect meal and insect lipid (BSFLO) had no discernible impact on the activity of the digestive enzyme trypsin and the level of total bile acids in the intestine of freshwater‐reared Atlantic salmon.…”
Section: Insect Lipid/oil As a Fo Or Other Terrestrial Oil Replacer I...mentioning
confidence: 99%
See 3 more Smart Citations
“…It is interesting to note that the dietary adjustments had no effect on the digestion of the majority of n−3 fatty acids (18:4n−3, 20:5n−3, 22:5n−3, and total n−3 fatty acids). Regarding the dietary insect oil inclusion effect on digestive enzyme activity in fish, Sudha et al 79 recently reported no significant change on amylase, lipase and protease activity in the intestine and liver of stripped catfish fed BSFLO compared with FO, MO, BCSO and FSO. Similar to this, Belghit et al 17 showed that dietary inclusion of insect meal and insect lipid (BSFLO) had no discernible impact on the activity of the digestive enzyme trypsin and the level of total bile acids in the intestine of freshwater‐reared Atlantic salmon.…”
Section: Insect Lipid/oil As a Fo Or Other Terrestrial Oil Replacer I...mentioning
confidence: 99%
“…For instance, because BSFLO contains linoleic, 18:2n−6, and linolenic, 18:3n−3, in concentrations similar to those of SBO and other vegetable oils, freshwater fish may be able to successfully use it to biosynthesize n−3 LC‐PUFA. Based on the published research, insect oil has been used with differing degrees of effectiveness to replace FO, SBO, moringa oil, sesame oil, flax seed oil, camelina oil, black cumin seed oil, and blends of terrestrial oils in the diets of different farmed fish species 14,23,44,78,79 . However, with all oil substitution work in aquaculture it is important also to look at the lipid content of the meal in the diet, especially FM.…”
Section: Insect Lipid/oil As a Fo Or Other Terrestrial Oil Replacer I...mentioning
confidence: 99%
See 2 more Smart Citations